Role of Research and Development in the evolution of Fishing Practices of Kerala Fishery Industry. (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper deals with the changes took place in the fisheries sector of Kerala due to the research and development in the fisheries sector with regard to the craft gear combinations and the changes in organisational set up in the fisheries sector. Research and development played a crucial role in the evolutionary process of fishing techniques of Kerala fishery industry. Hence, this paper is dealing with the major research and development phases and programmes which paved the way for the emergence of various craft gear combinations in the sector. The major developmental activities in this direction may be classified broadly under three periods: 1) 1953 to 1963 2)1963 to 1979 and 3) 1979 onwards.